Bumbas pārvaldīšanas paņēmienu izmantošanas labvēlīgā ietekme futbolistu attīstības sākumposmā - Jonāns, Einārs (Latvijas Universitāte, 2023)
Šajā darbā tiek aplūkota bumbas pārvaldīšanas paņēmienu izmantošanas ietekme uz sākuma sagatavošanas grupas audzēkņiem. Pētījuma mērķis- noskaidrot bumbas pārvaldīšanas paņēmienu izmantošanas ietekmi futbolistu attīstības sākumposmā. Tā noskaidrošanai izmantotas teorijas analīzes un pedagoģiskā novērojuma metodes. Pētījumā piedalījās 16 audzēkņi, kas 10 nedēļu garumā, paralēli grupu treniņiem, veica koordināciju vai bumbas pārvaldīšanas uzlabojošus uzdevumus.

This study investigated the effects of using ball handling techniques on the performance of students in the initial preparation group. The aim of the study was to clarify the impact of using ball handling techniques in the pilot stages of football players development. Theory analysis and pedagogical observation methods were used to clarify this. The study involved 16 students who performed coordination improving or ball-handling-improving tasks for 10 weeks in parallel with group training. Based on the available data, the author concluded that the study is ineffective in this way, as it does not provide the necessary information on the development trend in the groups. To be able to observe changes and to exclude the randomness of students' performance, the study should take place over a longer period of time.
The beneficial effects of using ball mastery techniques in the early stages of a football player's development
Keywords: Sporta zinātne; futbols; bumbas vadīšana; sākuma sagatavošanas grupa; bumbas pārvaldīšana